Antibiotic Sensitivity of Grapevine: A Comparison Between the Effect of Hygromycin and Kanamycin on Shoot Development of Transgenic 110 Richter Rootstock (Vi tis B erlandieri x Vi tis rupestris) - Torregrosa, L.; Lopez, G.; Bouquet, A. (South African Journal of Enology and Viticulture, 2017)
The effects of kanamycin and hygromycin on the in vitro development of 110 Richter rootstock (Vitis Berlandieri x V. rupestris) and derived transgenic clones were studied in order to evaluate their suitability as selectable markers for grapevine transformation. Transgenic clones carried both the neomycin phosphotransferase gene (nptll) under the nopaline synthase promoter (pNOS) and the hygromycin phosphotransferase (hpt) gene under the cauliflower mosaic virus 35S promoter (p35S), which confer the ability to grow in the presence of kanamycin and hygromycin, respectively. Even incorporated at low concentrations, both antibiotics strongly inhibited explant development for the control clone, but hygromycin appeared much more toxic. Whereas growth was stopped with 1 μg/mL hygromycin, 16 μg/mL kanamycin was required to block shoot development. Contrary to the control plants, transgenic clones exhibited a greater tolerance to hygromycin than kanamycin. In some transgenic clones the level of resistance conferred by the nptll was not significantly advantageous in terms of their ability to grow in the presence of kanamycin. Conversely, the hpt gene provided a strong level of tolerance to hygromycin in all transgenic clones, some clones developing up to 64 μg/mL hygromycin. Strategies for selection of grapevine putative transformants with these two antibiotics are discussed.